Pyoderma Gangrenosum: A Review of Clinical Features and Outcomes of 23 Cases Requiring Inpatient Management - Mingwei Joel Ye; Joshua Mingsheng Ye (Dermatology Research and Practice)
Pyoderma gangrenosum (PG) is a rare dermatological disorder characterised by the rapid progression of a painful, necrolytic ulcer. This study retrospectively identified patients who were admitted and treated for PG during a 10-year period (2003–2013). Twenty-three patients were included in this study, 16 women and seven men. The mean age at initial admission was 62.8 years (range 30 to 89 years). Lesions were localised to lower limb in 13 patients, peristomal region in four, breast in three, and upper limb in one, and two patients had PG at multiple sites. The variants of PG noted were ulcerative (18), bullous (2), vegetative (2), and pustular (1). Associated systemic diseases were observed in 11 patients (47.8%). Systemic therapies were initiated in 21 patients while two patients received topical treatments. The mean length of hospital stay was 47 days (range 5 to 243 days) and five patients died during their admissions. Seven patients required readmissions for exacerbations of their PG. Our study showed that patients admitted for treatment of PG had high morbidity and mortality. This study also highlights the importance of early and aggressive treatment of patients admitted with PG as well as treating associated systemic diseases and wound infections.